Pribumisasi Islam dalam Konteks Budaya Jawa dan Integrasi Bangsa - Mudhofir Abdullah (JURNAL INDO-ISLAMIKA, 2014)
Islam and the Javanese culture is a major theme which has become the discussion throughout of the archipelago. Centuries ago when Islam came to the archipelago, it was discussed with other great ideas such as Hinduism, Buddhism and the local religions. In contrast, the culture has been the legacy of the Javanese for thousands of years and continues to be enriched by world cultures. The relationship between Islam and the Javanese, therefore, attracted the interest of researchers and produced many academic works. Throughout its history, the relationship between Islam and the Javanese culture was not always harmonious. At times there were tensions and then at other moments there was consensus, the phenomenon was open and hidden. Such a paradox is referred to as the indigenization of Islam in Java. Indigenization of Islam is the transformation process of mutual borrowing between the outside elements and the locality. Indigenization of Islam is the articulation of socio-cultural interaction of Islam within the Javanese culture in the context of the nation-state: Islam must rise to higher levels as a means of achieving national unity. The paper discusses the indigenization of Islam in the context of the nation state.